Determining the financial performance of private veterinary practices - Höglund, Donald Lee, author (Colorado State University. Libraries, 1981)
Determining the financial performance of a private veterinary practice requires first and foremost that a private practice be considered as a business enterprise. Veterinarians, while facing a maze of normal business problems, have for the most part neglected any type of formal financial performance analysis. The collection and summarization of financial data in the veterinary practice is an essential prerequisite for analyzing financial performance. This collection and data summarization can be amassed conveniently and concisely in three commonly used financial statements: The Balance Sheet, The Income Statement, and The Statement of Changes in Financial Position. From here the actual analysis begins. Countless businesses in many industries utilize standard analytical techniques that provide business information for management decision making. Essentially, an analysis of the financial performance of the private veterinary practice is affected in three ways. First, the analyst calculates common-size percentages for all accounts on the balance sheet and income statement. Second, certain accounts are selected for an analysis of trend and growth rate, and third, a computation of certain relevant financial ratios is required for a comparison of accounts and account structure. Each of these three techniques can be performed for one instant in time and over several time frames thus allowing the veterinarian to compare his practice to other veterinary practices as well as to other similar industries. These analytical tools, while widespread in American business, are virtually non-existent in the veterinary industry. They should be computed and used for making managerial and financial decisions in the private veterinary practice.
Keywords: Veterinary medicine -- Practice; Veterinary medicine -- Economic aspects -- United States